2020
DOI: 10.2147/lra.s233274
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anesthetic Techniques: Focus on Lumbar Erector Spinae Plane Block</p>

Abstract: Defined in the last decade, erector spinae plane block (ESPB) is one of the more frequently used interfacial plans, and it has been the most discussed block among the recently defined techniques. Lumbar ESPB administered at lumbar levels is relatively novel and is a new horizon for regional anesthesia and pain practice. In this article, we aim to explain and introduce different approaches and explain the possible mechanism of action of lumbar ESPB. The objective of this review is to analyze the case reports, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 86 publications
0
35
0
Order By: Relevance
“…ESPB block is induced through injection of local anesthetic between the erector spinae muscle and the transverse process of the vertebrae (9)(10)(11). Upon injection, the anesthetic diffuses both cranially and caudally and acts on the dorsal rami of the spinal nerves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ESPB block is induced through injection of local anesthetic between the erector spinae muscle and the transverse process of the vertebrae (9)(10)(11). Upon injection, the anesthetic diffuses both cranially and caudally and acts on the dorsal rami of the spinal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Initially the use of ESPB was demonstrated for treating pain associated with shingles (9). It is a paravertebral interfascial block wherein the anesthetic is injected between the transverse process of the vertebrae and erector spinae muscle (10,11). Upon being injected, the anesthetic diffuses both cranially and caudally and exerts its action on the ventral and dorsal rami of the spinal nerves (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] Lumbar ESPB may lead to motor weakness, as local anesthetic can potentially spread anterior of the transverse process to the lumbar plexus and lumbar spinal nerves. [ 8 ] Interfascial blocks are volume dependent for spread, and the amount required differs on the region. Five milliliters at the vertebral level is indicated in the lumbar region versus 2.5 ml per thoracic level.…”
Section: Discussionmentioning
confidence: 99%
“…It was first applied to severe acute postoperative pain and neuropathic pain in 2016, and it was successful. Studies have shown that ESPB is easy to operate, has high safety, low error rate, good analgesic effect, and few adverse reactions, and shows broad clinical application prospects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%